GOOD CORPORATE GOVERNANCE, AUDITOR REPUTATION, AND COMPANY SIZE: ITS IMPACT ON THE TIMELINESS OF OF FINANCIAL REPORTS: GOOD CORPORATE GOVERNANCE, REPUTASI AUDITOR, DAN UKURAN PERUSAHAAN: DAMPAKNYA TERHADAP KETEPATAN WAKTU LAPORAN KEUANGAN - Rofika, Rofika; Candra, Alfino; Nasir, Azwir; Sofyan, Azhari (Universitas Riau, 2022)
The effectiveness of good corporate governance (GCG) processes, auditor reputation, and firm size are examined with regard to the timely submission of financial reports in this study. All trading firms listed on the Indonesian Stock Exchange (IDX) between 2017 and 2019 made up the study's population. The sample was selected using the purposive sampling method. The model chosen in this study was 44 companies selected based on the criteria. Logistic regression is the method used in the data analysis. According to the findings, the audit committee, independent commissioners, managerial ownership, and firm size had a big impact on how quickly financial statements were submitted. The institutions, ownership, and KAP's reputation, nevertheless, have no appreciable impact on how quickly financial reports are submitted